Reproductive behavior of Pantaneiros sheep, Mato Grosso do Sul, Brazil - Martins, Charles Ferreira; Santiago Filho, Arnaldo; Ferreira, Marcos Barbosa; Fernandes, Carlos Eurico dos Santos; Monreal, Antonio Carlos Duenhas; Souza, Carla Giselly de; Chagas, Renata Alves das; Vargas Junior, Fernando Miranda de (Acta Scientiarum. Animal Sciences, 2022)
The objective was to evaluate fertility, cyclicality behavior, and sexual performance of Pantaneiro sheep throughout the year’s photoperiods in Mato Grosso do Sul - Brazil. Two experiments were conducted. In experiment one, the ewes used aged between 2 and 4 years, distributed in three homogeneous groups of 54 animals and subjected to reproductive evaluation in three different predefined luminosity periods, consisting of autumn (11h 45 min.), spring (12h 30 min.), and summer (12h 55 min.). The characteristics studied were body weight (BW), body condition score (BCC), estrus distribution (EST), percentage of pregnant females per cycle (%P), plasma progesterone (PP), and fertility (F) in the three predefined seasons. The mating system used was controlled natural nocturnal and lasted for 45 days. Experiment two, evaluated the ram sexual activity. The males (10) were individually exposed to four ovariectomized ewes. The ewes cycled during evaluated seasons, and the highest fertility was observed in animals with BCC >2.75. The PP concentration differed among periods, and higher conception rates (F) were observed in autumn and spring. The rams (75%) had a medium of sexual performance when they performed more than two ejaculations in 20 min throughout the seasons. Pantaneiro sheep of both genders had a similar fertility index, with early and constant activity throughout the year, displaying no photoperiodism or seasonality.